2008
DOI: 10.1158/1078-0432.ccr-07-0986
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon–DNA Adducts in Prostate and Biochemical Recurrence after Prostatectomy

Abstract: Purpose: DNA adduct levels may be influenced by metabolic activity, DNA repair capabilities, and genomic integrity, all of which play a role in cancer progression. Experimental Design: To determine if elevated DNA adducts are a marker for prostate cancer progression, we measured polycyclic aromatic hydrocarbon^DNA adducts by immunohistochemistry in prostate cells of 368 surgical prostate cancer patients treated at the Henry Ford Hospital in Detroit, Michigan, between September 1999 and July 2004. Patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 51 publications
4
19
1
2
Order By: Relevance
“…Furthermore, because we previously observed that PAH-DNA adducts in prostate cells were associated with an increased risk of prostate cancer BCR [21], we also performed all of the aforementioned analyses with additional adjustment for PAH-DNA adduct levels in a subset of patients with PAH-DNA adduct data also available ( N  = 368); and we observed no material differences in any of the results presented (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because we previously observed that PAH-DNA adducts in prostate cells were associated with an increased risk of prostate cancer BCR [21], we also performed all of the aforementioned analyses with additional adjustment for PAH-DNA adduct levels in a subset of patients with PAH-DNA adduct data also available ( N  = 368); and we observed no material differences in any of the results presented (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…One other group of investigators has examined PAH-DNA adduct formation in human prostate, and prostate tumour, using IHC [61,62]. Semi-quantitative values for intensity of nuclear staining were obtained upon examination of 100 cells in tumour and non-tumour areas from the same specimen, and the data showed that PAH-DNA adducts were higher in Caucasians who smoked, compared with non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Formalin-fixed paraffin embedded (FFPE) prostate tissue of a subset of men who participated in the Gene-Environment Interaction in Prostate Cancer Study (GECAP) [22] and underwent prostatectomy for treatment of their cancer were selected for inclusion in this study. As part of the GECAP study, men completed a face-to-face interview to determine lifetime smoking history and occupational exposure to metals (Cd, Pb, and Zn), and completed a food frequency questionnaire.…”
Section: Methodsmentioning
confidence: 99%